Clinical significance of c-Met and phospho-c-Met (Tyr1234/1235) in ovarian cancer - Ling Lim; Chao-Chih Wu; Yun-Ting Hsu; Fang-Ju Sun; Chih-Long Chang (Elsevier, 2019)
Objective: c-Met is expressed in human ovarian cancer tissues, and its phosphorylation activates signaling cascades that might affect the behavior of cancer cells. In this study, we evaluated the association of c-Met and phosphorylated c-Met (phospho-c-Met) expressions with the clinical outcomes of ovarian cancer patients. Materials and methods: Archived tissue from surgical specimens of 269 ovarian cancer patients who underwent a debulking operation in MacKay Memorial Hospital between 2004 and 2012 were collected. Tissue microarrays were stained with anti-Met and anti-phospho-Met (Tyr1234/1235) monoclonal antibodies. Immunostaining intensity was scored on a scale of 0-3+. High expression was defined as more than 50% of moderate and intense staining. Patients' clinical data were reviewed until April 2017 for analysis. Results: The proportion of high c-Met expression was significantly higher in patients with cancer in early stages (Federation of Gynecology and Obstetrics stages I and II) and low histologic grades (grades 1 and 2) (79.70%, p = 0.0008 and 80.15%, p ≤ 0.0001, respectively). However, no association was found between phospho-c-Met and FIGO stage or the histologic grade. Ovarian clear cell carcinoma and mucinous carcinoma had much higher c-Met expression (95.16% and 87.10%, p ≤ 0.0001 and p = 0.0292, respectively). Although the overall survival did not differ significantly, low expressions of c-Met and phospho-c-Met were obviously associated with poor progression-free survival respectively (p = 0.0034, HR: 0.5264, 95% CI: 0.3326-0.8330 and p = 0.0136, HR: 0.5626, 95% CI: 0.3709-0.8535). Conclusion: Low c-Met expression was associated with poor clinical outcomes. Keywords: c-Met, phospho-c-Met, Ovarian cancer